Dinamika komunikasi pada keluarga yang memiliki istri berpenghasilan lebih dari suami - Ahmad Khairul Nuzuli; Ivan Sunata (Fakultas Ilmu Komunikasi Universitas dr. Soetomo, 2022)
Marriage is a human nature where the individual goes through the human cycle and becomes a family. In marriage, women tend to be placed in the domestic sphere, while men are placed in the public sphere. Along with the times, many women have entered the public work sector and often women's income is higher than men's. The wife's income which is greater than the husband's in a family often becomes one of the conflicts in the household. This study aims to look at the dynamics of communication in families whose wives earn more than their husbands. The method used is descriptive qualitative with a phenomenological approach. The results of the study show that what needs to be considered in the division of roles is mutual understanding and respect from partners. The thing that needs to be considered in maintaining harmony is the intensity of communication which aims to increase mutual understanding between partners.